THE ROLE OF LISTING REQUIREMENTS IN INVESTMENT ACTIVITY (Spectrum Journal of Innovation, Reforms and Development, 2024)
The article discusses the introduction of listing requirements by stock exchanges and its impact on the activities of joint-stock companies. The types of listings, their nature, and levels used in the stock markets of the Russian Federation and the Republic of Uzbekistan were studied. The trends in the development of the activities of joint stock companies on the stock market of Uzbekistan and the directions for its further improvement have been identified.